2019
DOI: 10.1021/acs.jpcc.9b01111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrated and Nonhydrated Choline Chloride–Urea Deep Eutectic Solvent (Reline) on Thrombin-Binding G-quadruplex Aptamer (TBA): A Classical Molecular Dynamics Simulation Study

Abstract: Guanine-rich quadruplex nucleic acid (G-DNA) sequence is highly polymorphic. The obtained structure of G-DNA is exquisitely impressible to its sequence and the chemical environment. Due to its controllable different structures, G-DNA has acquired much attention in various research areas such as nanotechnology, medicinal chemistry, and molecular biology. However, the applications of G-DNA are mainly restricted to the aqueous media, although a large number of important chemical reactions, nanodevices, etc. have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 105 publications
1
23
0
Order By: Relevance
“…The band offset at the interface of MAPbI 3 /MA 3 Sb 2 I 9 is estimated with aid of first‐principles calculation. The layer‐resolved density of states (DOSs) in Figure 3d demonstrate that 2D‐MA 3 Sb 2 I 9 exhibits p‐type conductivity, as its Fermi energy is closer to MA 3 Sb 2 I 9 VBM, which is consistent with the reported results [ 28,40 ] and the UPS measurements in Figure 3a. Hybridized I(5p) and Sb(5s) orbitals contribute MA 3 Sb 2 I 9 VBM, higher than the MAPbI 3 VBM; the calculated MA 3 Sb 2 I 9 CBM is much higher than the CBM of the MAPbI 3 layer.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…The band offset at the interface of MAPbI 3 /MA 3 Sb 2 I 9 is estimated with aid of first‐principles calculation. The layer‐resolved density of states (DOSs) in Figure 3d demonstrate that 2D‐MA 3 Sb 2 I 9 exhibits p‐type conductivity, as its Fermi energy is closer to MA 3 Sb 2 I 9 VBM, which is consistent with the reported results [ 28,40 ] and the UPS measurements in Figure 3a. Hybridized I(5p) and Sb(5s) orbitals contribute MA 3 Sb 2 I 9 VBM, higher than the MAPbI 3 VBM; the calculated MA 3 Sb 2 I 9 CBM is much higher than the CBM of the MAPbI 3 layer.…”
Section: Figuresupporting
confidence: 89%
“…2D antimony halide perovskites A 3 Sb 2 I 9 (A = Cs, MA) is reported to process more favorable optoelectronic property than 0D‐A 3 Sb 2 I 9 and bismuth‐based perovskite A 3 Bi 2 I 9 . [ 28–31 ] It is observed that MA 3 Sb 2 I 9 causes a downshift of Fermi energy level to the valence band maximum (VBM), thus changing the MAPbI 3 surface to be more p‐type. SnO 2 /MAPbI 3 /MA 3 Sb 2 I 9 /Spiro‐OMeTAD constructs an n–i–p–p + heterojunction ( Figure a), where MA 3 Sb 2 I 9 serves as BSF to effectively promote hole extraction.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[71,72] Moreover, the significance of inter-peptide hydrogen bonds is vital with regards to the aggregation of peptides, which leads to the formation of different shapes of the peptides. To find the role of hydrogen bond in these four peptides aggregation, we have calculated the average number of hydrogen bonds using the geometric criteria [73,74] : (a) the distance between donor and acceptor is less than or equal to 3.5 Å, and simultaneously, (b) donor-acceptor-hydrogen lowing previous studies, [75][76][77] although some lower probability has been observed in Q αR region for both isoleucine and valine residue. For peptide 2, the backbone φ/ψ angles have been noticed in mostly Q β quadrant region along with slightly higher probability has been noticed in Q αR region for both the residues that are comparably higher than the peptides, 1 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Mamajanov et al demonstrated that at least four distinct nucleic acid secondary structures can exist in DESs; they also noted that the anhydrous character and capacity to support natively folded DNA and protein structures make DESs appealing for the synthesis of biopolymers [ 52 ]. Pal et al examined the interaction between reline and guanine-rich quadruplex thrombin-binding aptamer (TBA) at 300 K for different reline concentrations [ 53 ]. They studied the conformational behavior of the aptamer in reline using molecular dynamics simulations.…”
Section: Biocompatibility Of Dessmentioning
confidence: 99%